2002
DOI: 10.1002/j.2050-0416.2002.tb00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Malting Performance of Normal Huskless and Acid-Dehusked Barley Samples

Abstract: Sulphuric acid dehusked barley had a higher germinative energy and lower microbial infection than normal huskless (naked) barley, suggesting that the pericarp layer harboured microbial infection which may have limited the germination rate. Dehusking the normal huskless barley using sulphuric acid resulted in lower microbial infection, and increased germinative energy. The normal huskless barley sample had a higher b-glucan content than the acid-dehusked barley and had slower b-glucan breakdown during malting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
1
16
1
3
Order By: Relevance
“…It was, however, considered that this material would most likely be applicable in malt distilleries using a wort filter, rather than a mash tun. Studies also showed that hull-less barley appeared to have higher levels of β-glucan than husked barley 5,13 . If a suitable enzyme-rich hull-less malt could be produced, this could potentially find an application in the grain distillery, and the intrinsic high alcohol yield from the malt would enhance distillery yield.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was, however, considered that this material would most likely be applicable in malt distilleries using a wort filter, rather than a mash tun. Studies also showed that hull-less barley appeared to have higher levels of β-glucan than husked barley 5,13 . If a suitable enzyme-rich hull-less malt could be produced, this could potentially find an application in the grain distillery, and the intrinsic high alcohol yield from the malt would enhance distillery yield.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant advances in the use of barley was the development of hull-less barley types which might be suitable for use in the production of Scotch whisky. Some studies carried out on hull-less barleys appear to suggest that they contain important brewing qualities, especially with regard to high extract recovery from the malt 5,13 . Also, previous work at the Scotch Whisky Research Institute (SWRI), looking at an early type of hull-less barley, has shown that the use of malt from this type of barley can provide substantially higher alcohol yields, compared with conventional barley malt.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two obstacles have been identified, however, the first being the protective function of the husk 19 in avoiding damage to the embryo during grain handling, which could lead to poor or uneven germination during malting 5 . However, views on the severity of this problem differ and some studies show malts, from hull-less barleys, to have modified as well as the husked controls 13,20 .…”
Section: Introductionmentioning
confidence: 99%